RNF112 Facilitates Ubiquitin‐Mediated Degradation of c‐Myc, Suppressing Proliferation, Migration and Lipid Synthesis in Bladder Cancer - Kangping Xiong; Siming Chen; Huimin Xu; Sheng Tu; Hong Weng; Yejinpeng Wang; Mingxing Li; Jingtian Yu; Kaiyu Qian; Lingao Ju; Yi Zhang; Yu Xiao; et al. (Advanced Science)
Abstract The E3 ubiquitin ligase RNF112 is significantly downregulated in bladder cancer (BLCA) and is correlated with disease progression. In vitro and in vivo studies indicated that RNF112 suppresses BLCA cell proliferation, migration, and lipid synthesis. Mechanistically, RNF112 directly interacts with the MB II domain of MYC through its N‐terminal zinc finger motif, and its catalytic site C97 facilitates K48‐linked polyubiquitination of the K389 residue on the c‐Myc protein, accelerating its degradation. Additionally, this research validated the interaction of c‐Myc with the promoter of ATP citrate lyase (ACLY), a central enzyme of lipid metabolism, promoting its transcriptional activity. The restoration of c‐Myc or ACLY expression attenuated the inhibitory effects of RNF112 on BLCA cell growth, migration, and lipid synthesis. In conclusion, this study confirmed that RNF112 suppressed the proliferation, migration, and lipid synthesis of BLCA cells by facilitating the ubiquitin‐mediated degradation of c‐Myc.